46 Overestimation of depression prevalence in meta-analyses via the inclusion of primary studies that assessed depression using screening tools or rating scales rather than validated diagnostic interviews. (20th August 2018) - Levis, Brooke; Yan, Xin Wei; He, Chen; Bendetti, Andrea; Thombs, Brett D
Abstract : Objectives: Estimates of the prevalence of depression should be based on validated diagnostic interviews to determine case status and not depression screening tools or symptom rating scales, which are not intended for this purpose. Using cutoff scores from screening or rating scales to estimate prevalence tends to over-estimate prevalence substantially, particularly in low-prevalence groups (Thombs et al, CMAJ, 2018). Authors of meta-analyses, however, sometimes base estimates of depression prevalence on depression screening tools or rating scales. The objectives of this study were to (1) determine what depression ascertainment methods are commonly used to classify cases of depression in primary studies included in meta-analyses of depression prevalence; (2) determine what terminology is used in meta-analyses to describe prevalence rates based on different methods; and (3) examine the extent to which including studies that count positive screens as cases results in the overestimation of depression prevalence in recent meta-analyses of depression prevalence. Method: We searched PubMed from 2008–2017 for meta-analyses that reported pooled prevalence of depression in the abstract. For each included meta-analysis, we recorded whether the abstract reported a pooled prevalence based on primary studies that used (1) diagnostic interviews only, (2) screening tools or rating scales only, and (3) a combination of diagnostic interviews, screening tools or rating scales, and other methods (e.g., chart diagnoses, self-report). If multiple prevalence estimates were reported for a category (e.g., for different subgroups), we extracted data only for the first prevalence estimate in the category. For each meta-analysis, for each prevalence estimate, we recorded whether the abstract indicated the types of ascertainment methods included, the terminology used to describe the prevalence value, and the number of studies pooled, the pooled sample size, and the pooled prevalence. For the combination category, we determined how many pooled primary studies used a validated diagnostic interview. Results: 69 eligible articles were included, and 81 pooled prevalence estimates were extracted (9 for diagnostic interviews only, 36 for screening tools or rating scales only, 36 for combinations). Mean pooled prevalence was 17% for interviews only, 31% for screening tools or rating scales only, and 22% for combinations. Among 11 articles that reported prevalence for interviews or for combinations and also for screening tools or rating scales, prevalence was always higher based on screening tools or rating scales. Only 10 of 36 meta-analyses that combined studies that used screening tools or rating scales indicated this in the abstract; 22 of 36 referred to the prevalence as for 'depression' or a 'depressive disorder', despite using screening or rating tools. 5 studies that did not report a prevalence based on diagnostic interviews in the abstract provided one in the text; on average, it was half the value reported in the abstract. Conclusions: Most meta-analyses of depression prevalence combine prevalence estimates from primary studies that used methods other than validated diagnostic interviews to assess depression. Some meta-analyses describe the resulting pooled prevalence as prevalence of 'depressive symptoms', but most describe prevalence of 'depression' or 'depressive disorders' despite not assessing disorders. Among 69 included meta-analyses, prevalence of depression was always higher when based on depression screening tools or rating scales than when based on diagnostic interviews or a combination of ascertainment methods. Including studies that assess depression based on methods other than validated diagnostic interviews exaggerates the true prevalence of depression. These are preliminary results. Final results will include, for the combination category, a comparison of published prevalence estimates and prevalence estimates based on re-analysis using only the studies that assessed depression using a validated diagnostic interview.